New approach to the optimization problem - Amaral, João Ferreira do (2021)
A new approach to the problem of optimization is developed using tools such as the concepts of aggregate and of combined functions. The solving of a simple problem of calculus of variations with inequality constraints illustrates the potentiality of this new method.